COMMON FIXED POINTS OF GENERALIZED CO-CYCLIC WEAKLY CONTRACTIVE MAPS - Babu, G. V. R.; Sarma, K. K. M.; Kumari, V. A. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2019)
In this paper, we introduce generalized co-cyclic weakly contractive maps and prove the existence of common fixed points in complete metric spaces. We deduce some corollaries from our main results and provide examples in support of our results.